Biological cycle of Argas (Persicargas) keiransi fed on hen´s blood under laboratory conditions - Ardiles, Karen (2013)
A. keiransi Estrada-Peria, Venzal & Gonzalez-Acufia (Acari: Argasidae) be-long to the subgenus Persicargas, which includes soft bodied ticks distributed worldwide and commonly found parasitizing birds (Klompen, 1992). Argas (Persicargas) keiransi was described from engorged larvae of the Chimango Caracara (Milvago chimango chimango Vieillot (Ayes: Falconiformes: Falconi-dae: Caracarinae)) from Chillan (Bio Bio Region), Chile (Estrada-Pena et al. 2003). Females of A. keiransi were later described by Estrada-Pefla et al. (2006), also based on specimens from Chillan. The objective of this study was to describe the biological cycle of A. keiransi under laboratory conditions and compare it with related species.